2001
DOI: 10.1046/j.1524-4741.1998.410062.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: Knowledge, Attitudes, and Practices of Female Schoolteachers in Lagos, Nigeria

Abstract: This article examines the knowledge, attitudes, and practices of female schoolteachers concerning breast cancer. A cross-sectional survey was conducted among 200 schoolteachers randomly selected from 12 schools in Lagos, Nigeria. A self-administered questionnaire was used to investigate their knowledge about the symptoms of breast cancer, methods of diagnosis, risk factors, and breast self-examination. A response rate of 94% (188 respondents) was achieved. Eighty-five percent knew breast cancer was a serious d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
54
4
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 10 publications
16
54
4
2
Order By: Relevance
“…These result were near to that reported in study done by Adebamowo and Ajayi, (2000) [21]; Odusanya, (2001) [28]; Adebamowo and Adekunle, (1999) [29], where these studies have shown that the incidence of breast cancer is said to be slightly higher in persons that have first degree relatives with a history of breast cancer, persons that have early menarche and late menopause and those that use oral contraceptives, persons do not breast feed and those women having their first birth after age 35 or nulliparous women. The incidence is also increased with increasing age of the patient, smoking, obesity, physical inactivity, radiation exposure, intake of alcohol and high fat.…”
Section: Discussionsupporting
confidence: 83%
“…These result were near to that reported in study done by Adebamowo and Ajayi, (2000) [21]; Odusanya, (2001) [28]; Adebamowo and Adekunle, (1999) [29], where these studies have shown that the incidence of breast cancer is said to be slightly higher in persons that have first degree relatives with a history of breast cancer, persons that have early menarche and late menopause and those that use oral contraceptives, persons do not breast feed and those women having their first birth after age 35 or nulliparous women. The incidence is also increased with increasing age of the patient, smoking, obesity, physical inactivity, radiation exposure, intake of alcohol and high fat.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is similar to the study [15]. The poor level of knowledge found in this study is in keeping with reports of other investigators [6,7,8]. In a survey of breast cancer knowledge, Uche [8] noted that only 32% of the respondents knew that a breast lump was a warning sign for breast cancer, 58.5% were unaware of the most warning signs and only 9.8% knew of methods of detecting breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Seventy percent of Nigerian women present with advanced staged disease while the five-year survival rate is less than 10% compared with over 70% in Western Europe and North America [5]. Odusanya found BRCA to be the most common surgical condition women worry about in a list of eleven comparable conditions [6]. According to Odusanya, BRCA is not well understood by women and there is a need for information and enlightenment if they are to present early in hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation indicated that only 32.5 percent could correctly described the procedure. Several studies on BSE such as have reported similar findings [13]. This may be as a result of poor health education in our society and also the perception that they cannot develop breast cancer.…”
Section: Discussionmentioning
confidence: 70%